The Students’ Ability in Analyzing Metafunction - Siregar, Sri Rahmadhani (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
This research aimed to know the category of students’ ability in analyzing metafunction that was a subject in discourse analysis. This research included into quantitative research. The population were all the students of TBI seventh semester in 2018/2019 academic year counted 90 students. Random sampling was used to get 60 students. The instrument to collect data was used test. The finding of the research was the students’ ability in analyzing metafunction included into very good category.